Diagnosing Asthma: The Fit between Survey and Administrative Database - Lisa Huzel; Leslie L Roos; Nick R Anthonisen; Jure Manfreda (Canadian Respiratory Journal)
BACKGROUND:Standard methods for population studies of asthma include surveying population samples using questionnaires and examining people in laboratories. These procedures are extremely expensive. It would be helpful if, at least for some purposes, they could be replaced by cheaper techniques with adequate validity. OBJECTIVES: To determine agreement between survey and database in regard to the prevalence of asthma.